The impact of adding nano zirconium dioxide fillers on color change, water sorption and solubility for denture liners - Gulfem Ergun; Ayşe Seda Ataol; Zeynep Şahin; Rükan Genç Altürk (Gazi University, 2022)
Objective: Zirconium dioxide (ZrO2) nanofillers were added to denture liners to improve their physical properties. The main goal of this research was to evaluate the impact of adding nano zirconium oxide (ZrO2) fillers on color change, water sorption and solubility of silicone and acrylic denture liners. Materials and Method: The surface of ZrO2 nanoparticles was modified via treatment with the silane coupling agent (3-aminopropyl) triethoxysilane. Fourier transform infrared spectroscopy analysis was performed to characterize surfaces untreated or treated with ZrO2. After modification, these nanoparticles were incorporated into silicone and acrylic denture liners. Three subgroups were assigned for each test method. Kruskal-Wallis and Mann-Whitney U tests were used for the statistical analysis (p ≤ 0.05). Results: Water sorption and solubility in water values decreased with the addition of modified ZrO2 nanofiller in both test groups (respectively, acrylic-based tissue conditioner: p = 0.040 and p = 0.020; silicone-based denture liner: p < 0.001 and p = 0.017). The acrylic-based tissue conditioner test group with 1% modified ZrO2 nanofiller showed the greatest color change (ΔΕ = 37.94 ±6.62), whereas the silicone-based denture liner group with 0.5% modified ZrO2 nanofiller presented the lowest (ΔΕ = 5.02 ±2.30). Conclusion: Modified ZrO2 nanofiller-incorporated silicone-based denture liners might show better clinical success than acrylic ones according to the evaluated parameters.